Novel mutation in TSPAN12 leads to autosomal recessive inheritance of congenital vitreoretinal disease with intra‐familial phenotypic variability. Issue 12 (22nd September 2014) - Gal, Moran; Levanon, Erez Y.; Hujeirat, Yasir; Khayat, Morad; Pe'er, Jacob; Shalev, Stavit
<x xml:space="preserve">Abstract</x> Developmental malformations of the vitreoretinal vasculature are a heterogeneous group of conditions with various modes of inheritance, and include familial exudative vitreoretinopathy (FEVR), persistent fetal vasculature (PFV), and Norrie disease. We investigated a large consanguineous kindred with multiple affected individuals exhibiting variable phenotypes of abnormal vitreoretinal vasculature, consistent with the three above‐mentioned conditions and compatible with autosomal recessive inheritance. Exome sequencing identified a novel c.542G > T (p.C181F) apparently mutation in the TSPAN12 gene that segregated with the ocular disease in the family. The TSPAN12 gene was previously reported to cause dominant and recessive FEVR, but has not yet been associated with other vitreoretinal manifestations. The intra‐familial clinical variability caused by a single mutation in the TSPAN12 gene underscores the complicated phenotype‐genotype correlation of mutations in this gene, and suggests that there are additional genetic and environmental factors involved in the complex process of ocular vascularization during embryonic development. Our study supports considering PFV, FEVR, and Norrie disease a spectrum of disorders, with clinical and genetic overlap, caused by mutations in distinct genes acting in the Norrin/β‐catenin signaling pathway. © 2014 Wiley Periodicals, Inc.